Effect of 16% Carbamide Peroxide and Activated-Charcoal-Based Whitening Toothpaste on Enamel Surface Roughness in Bovine Teeth: An In Vitro Study - Zamudio-Santiago, Jorge (2023)
Background: Activated charcoal is a nanocrystalline form of carbon with a large specific surface area and high porosity in the nanometer range, having consequently the capacity to absorb pigments, chromophores, and stains responsible for tooth color change, while carbamide peroxide is unstable and breaks down immediately upon contact with tissue and saliva, first dissociating into hydrogen peroxide and urea and subsequently into oxygen, water, and carbon dioxide. Therefore, the aim of the present study was to assess the effect of 16% carbamide peroxide and activated-charcoal-based whitening toothpaste on enamel surface roughness in bovine teeth. Materials and Methods: The present experimental in vitro, longitudinal, and prospective study consisted of 60 teeth randomly distributed in six groups: A: artificial saliva, B: conventional toothpaste (Colgate Maximum Protection), C: whitening toothpaste with activated charcoal (Oral-B 3D White Mineral Clear), D: 16% carbamide peroxide (Whiteness Perfect 16%), E: 16% carbamide peroxide plus conventional toothpaste (Whiteness Perfect 16% plus Colgate Maximum Protection), and F: 16% carbamide peroxide plus whitening toothpaste with activated charcoal (Whiteness Perfect 16% plus Oral-B 3D White Mineral Clear). Surface roughness was assessed with a digital roughness meter before and after each treatment. For the statistical analysis, Student’s t test for related samples was used, in addition to the ANOVA test for one intergroup factor, considering a significance level of p < 0.05. Results: The surface roughness variation of bovine tooth enamel, before and after application of bleaching agent, was higher in groups of whitening toothpaste with activated charcoal (0.200 µm, Confidence Interval (CI): 0.105; 0.296 µm) and 16% carbamide peroxide plus whitening toothpaste with activated charcoal (0.201 µm, (CI): 0.092; 0.309 µm). In addition, bovine teeth treated with conventional toothpaste (p = 0.041), whitening toothpaste with activated charcoal (p = 0.001), and 16% carbamide peroxide plus whitening toothpaste with activated charcoal (p = 0.002) significantly increased their surface roughness values. On the other hand, significant differences were observed when comparing the variation in surface roughness between the application of artificial saliva (control) and the whitening toothpaste with activated charcoal (p = 0.031), and the 16% carbamide peroxide plus whitening toothpaste with activated charcoal (p = 0.030). Conclusion: The use of whitening toothpaste with activated charcoal and in combination with 16% carbamide peroxide significantly increased enamel surface roughness in bovine teeth.